The pharciceratid ammonoids from the Roteisenstein Formation of Dillenburg (Cephalopoda, Ammonoidea) - Korn, Dieter; Bockwinkel, Jürgen (European Journal of Taxonomy, 2021)
The ammonoids of the suborder Pharciceratina from the Red Ironstone Formation of the area around Dillenburg (eastern Rhenish Mountains) are revised, mainly based on historical collections stored in the Museum für Naturkunde, Berlin. The genus Evopharciceras gen. nov. and the following species are newly described: Maenioceras ornatum sp. nov., Pharciceras beyrichi sp. nov., Pharciceras kruegeri sp. nov., Pharciceras ferrum sp. nov., Evopharciceras formosum gen. et sp. nov., Extropharciceras metallicum sp. nov., Lunupharciceras kochi sp. nov., Stenopharciceras lotzi sp. nov., Pluripharciceras ahlburgi sp. nov. and Sandbergeroceras archiaci sp. nov. Neotypes are proposed for the species Extropharciceras becheri (von Buch, 1832) and Sandbergeroceras costatum (d’Archiac & de Verneuil, 1842). The stratigraphic distribution of the genera is discussed; they are assigned to three assemblages: (1) Maenioceras terebratum Zone (early Givetian; two species), (2) Pseudoprobeloceras pernai Zone (latest Givetian; fifteen species) and (3) Sandbergeroceras costatum Zone (early Frasnian; three species).